Adoption of chilli Production Technology Among the chilli Growers in Sehore District of Madhya Pradesh - Sharma, Abhilasha; singh, Mukesh; Sharma, S. N.; Tambe, S. B. (Indian Journal of Extension Education, 2015)
This study was conducted in Sehore district of Madhya Pradesh in the year of 2013-14. The study revealed that majority  of the chilli growers had high adoption behaviour (46.08%) followed by medium level of adoption(36.42%) and low  adoption behavior ( 17.50%) regarding overall recommended chilli production technology respectively. The study also  revealed that the socio-economic factors had positive and significant influence on the adoption of chilli production  technology, among the chilli growers .
Keywords: Chilli growers; adoption behaviour; production technology; constraints